Review of Transition Metal Dithiocarbamate Complexes: Novel Fluorescent Materials for Biosensor Applications - Irfandi, Rizal (Hayyan Journal, 2025)
Transition metal complexes with dithiocarbamate ligands have attracted significant attention in recent decades due to their unique electronic and optical properties. This article presents a comprehensive review of transition metal-dithiocarbamate complexes as fluorescent materials and their potential in biosensor development. Focus is given on their chemical structure, fluorescence mechanism, as well as their application in detecting important biomolecules. With the increasing need for sensitive, selective, and low-cost biosensors, these materials offer promising prospects in various biomedical and environmental applications.